The Global Economic Crisis: The Question of ‘ME’ against ‘US’ - Raja Khurrum, Nadeem (2009)
This study looks into state of economies of India, Japan and United States of America. Using stock indices, net exports and industrial production indices we gauge the financial and real economic health with respect to that of each other during the American born subprime initiated global financial crises. To investigate the impact of the current US financial crisis on these markets we split the study into two sub-periods: pre-crisis (2003-2006) and post-crisis (2006-2009) in the post crisis era I have created another sub section to make the analysis more clear that is after the crash of Lehman brothers (Sep’ 08- 2009). I set the mean of the changes equal to see how much each economy has deteriorated by itself and with respect to the other two economies. I found that the variables I took out of them India has managed to maintain and significantly improve its industrial production index and the United States has had a sharp decrease in the ever swelling trade deficit, which on further investigation smells of protectionism. It seems that the world leaders are not learning much from the crisis and taking on a short term view by taking on protectionist measures to safe guard their domestic economy, it was such short sightedness that caused the crisis could this hastiness cause even a worse crisis, this time not economic but political or maybe social.